2016
DOI: 10.1016/j.ijrobp.2016.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Reirradiation of Prostate Cancer Local Failures After Previous Curative Radiation Therapy: Long-Term Outcome and Tolerance

Abstract: SummaryIn this retrospective study we evaluated the long-term results of 14 prostate cancer patients treated with salvage external beam radiation therapy (EBRT) for exclusive local failure after primary EBRT. Whole-gland reirradiation resulted in a high rate of severe radiationinduced side effects and poor long-term biochemical and local control. Alternative salvage reirradiation modalities should be explored for selected cases of local relapse in accurately designed prospective trials.Purpose: To evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 18 publications
2
35
1
Order By: Relevance
“…There were no increased urinary or digestive toxicity in these patients compared to those who had not previously been irradiated. These results are coherent with those from the other studies that considered pelvic reirradiation using stereotactic body radiotherapy [15]- [17] or even within the context of salvage WPRT directed by FCH-PET imaging [8]. Further study of the repair mechanisms in radiation injury to the pelvic tissues, and hence the feasibility of reirradiation, is highly recommended.…”
Section: Discussionsupporting
confidence: 84%
“…There were no increased urinary or digestive toxicity in these patients compared to those who had not previously been irradiated. These results are coherent with those from the other studies that considered pelvic reirradiation using stereotactic body radiotherapy [15]- [17] or even within the context of salvage WPRT directed by FCH-PET imaging [8]. Further study of the repair mechanisms in radiation injury to the pelvic tissues, and hence the feasibility of reirradiation, is highly recommended.…”
Section: Discussionsupporting
confidence: 84%
“…The efficacy of salvage reirradiation for locally recurrent PCa has been evaluated by several investigations. [14][15][16][17][18][19][22][23][24][25][26][28][29][30][31][32][33][34] The first report on re-EBRT by Vavassori et al 15 including six cases treated by CyberKnife, showed the feasibility of reirradiation with an acceptable rate of acute and early chronic toxicity (median follow-up was 11.3 months). These preliminary findings were then confirmed by the successive series.…”
Section: Discussionmentioning
confidence: 99%
“…14,[16][17][18][19][28][29][30][31][32][33][34] All but one report concluded that salvage re-EBRT is safe. [14][15][16][17][18][19][20][21][23][24][25][26][27] Zilli et al 22 published the data of 14 patients treated with whole prostate reirradiation, with the median follow-up of 94 months, showing low acute but very high late GU and GI toxicity rates (29% of patients experienced combined Grade 4 GU/GI injury). Contrarily to the Zilli's series, we observed only 1 Grade 3 GU event among 20 males with follow-up >36 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using advanced imaging (recurrence identified by magnetic resonance, staging based on [ 18 F]-fluorocholine positron emission tomography), highly selective radiotherapy modalities (stereotactic body radiotherapy and image-guided intensity-modulated radiotherapy), and extreme hypofractionation (doses > 6 Gy/fraction), Janoray et al showed that reirradiation is safe and may offer a medium-term cure in a good proportion of patients. By contrast, a report on reirradiation using conventional techniques and conventional fractionation (2 Gy/fraction) to the full radiation dose showed unacceptable toxicity and unsatisfactory tumor control [4]. These small but important series add new data to the current view of radiotherapy issues for prostate cancer: high fractionation sensitivity is an intrinsic property of primary prostate cancer, and there is now growing evidence that the same approach may work for radiationrecurrent cancer.…”
Section: Expert's Summarymentioning
confidence: 96%